CIVIL FORFEITURE SEBAGAI UPAYA PENGEMBALIAN KERUGIAN NEGARA PADA TINDAK PIDANA KORUPSI - Pradani Tyas Septiana; Wiwik Afifah (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Corruption is one of the causes of poverty in many countries, including Indonesia. Corruption causes state losses, so that the return of state financial losses must be carried out by corruptors to restore the Indonesian economy. The mechanism for recovering state financial losses has been regulated in Indonesia through criminal and civil channels. However, the implementation has not been optimally carried out by the State. Based on this, this study aims to determine the concept of civil forfeiture in returning state losses from corruption. The research method used is normative juridical. The results of the study state that in Indonesia the concept of returning state losses is based on criminal charges carried out by the Public Prosecutor and then executed by investigators, while the concept of civil forfeiture is carried out in a civil manner, where civil claims are carried out simultaneously with criminal charges. This is implemented in the United States, and in Indonesia it has the potential to apply it so that the return of state financial losses can be carried out optimally